Exploring Lycopene: A Comprehensive Review on its Food Sources, Health Benefits and Functional Food Applications - Gengatharan, Ashwini; Che Zahari, Che-Nur-Mazadillina; Mohamad, Nur-Vaizura (Current Nutrition & Food Science, 2024)
The importance of dietary composition to human health has raised consumer interest in consuming fruits, vegetables, and foods containing bioactive chemicals and nutraceuticals. Lycopene belongs to the carotenoids abundantly found in tomato and tomato-based food products. It also can be present in other types of fruits like watermelon and pink guava. This review aims to outline the lycopene sources, health benefits, their applications as functional food ingredients and the challenges to commercialization. It has been reported that dietary lycopene has multifunctional health activities, including anticancer on various types of cancer, hepatoprotective, neuroprotective, and bone protective effects identified in clinical and preclinical studies. This is because, lycopene primarily affects oxidative stress, inflammation, and pathways implicated in carcinogenesis and cell proliferation. The effects of preparation and processing factors that may impair the bioavailability of lycopene consumed through diet are addressed in this review. Overall, lycopene is a valuable natural colourant that can enhance the nutritional value of foods leading to the development of new functional foods in the food industry.
Keywords: lycopene